Role of glial cells in motor neuron degeneration in hereditary spastic paraplegias - Vijayaraghavan, Manaswini; Murali, Sarvika Periyapalayam; Thakur, Gitika; Li, Xue-Jun (Frontiers in Cellular Neuroscience, 2025)
This review provides a comprehensive overview of hereditary spastic paraplegias (HSPs) and summarizes the recent progress on the role of glial cells in the pathogenesis of HSPs. HSPs are a heterogeneous group of neurogenetic diseases characterized by axonal degeneration of cortical motor neurons, leading to muscle weakness and atrophy. Though the contribution of glial cells, especially astrocytes, to the progression of other motor neuron diseases like amyotrophic lateral sclerosis (ALS) is well documented, the role of glial cells and the interaction between neurons and astrocytes in HSP remained unknown until recently. Using human pluripotent stem cell-based models of HSPs, a study reported impaired lipid metabolisms and reduced size of lipid droplets in HSP astrocytes. Moreover, targeting lipid dysfunction in astrocytes rescues axonal degeneration of HSP cortical neurons, demonstrating a non-cell-autonomous mechanism in axonal deficits of HSP neurons. In addition to astrocytes, recent studies revealed dysfunctions in HSP patient pluripotent stem cell-derived microglial cells. Increased microgliosis and pro-inflammation factors were also observed in HSP patients’ samples, pointing to an exciting role of innate immunity and microglia in HSP. Building upon these recent studies, further investigation of the detailed molecular mechanism and the interplay between glial cell dysfunction and neuronal degeneration in HSP by combining human stem cell models, animal models, and patient samples will open avenues for identifying new therapeutic targets and strategies for HSP.